2010
DOI: 10.2224/sbp.2010.38.3.381
|View full text |Cite
|
Sign up to set email alerts
|

The perception of menarche and menstruation among Turkish married women: Attitudes, experiences, and behaviors

Abstract: The aim in this study was to determine the experiences, behaviors, and attitudes of married Turkish women of fertility age, towards menstruation. Of the 586 women who took part in the study 64.2% described their menarche as an unfavorable experience. A total of 48.8% of them felt they had to keep their menstruation as a secret, and 2.2% believed that menstruating was a punishment given by God. Most did not approve of religious observances such as reciting the Quran, performing the namaz, and fasting when mens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
11
0
3
Order By: Relevance
“…When asked whether they were comfortable talking to their fathers regarding menses, majority (82%) said that they are not while a study conducted by Cevirme et al revealed that 48.8% females hide the fact that they are menstruating from other people especially men 25 .…”
Section: Discussionmentioning
confidence: 99%
“…When asked whether they were comfortable talking to their fathers regarding menses, majority (82%) said that they are not while a study conducted by Cevirme et al revealed that 48.8% females hide the fact that they are menstruating from other people especially men 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Women often refer to menstruation in negative terms as shameful and embarrassing (Çevirme et al, 2010;Lee, 2009). Negative feelings surrounding menstruation are also expressed when EXPERIENCES OF MENSTRUATION DURING A LIFESPAN 4 having sexual intercourse during menstrual bleeding.…”
mentioning
confidence: 99%
“…Some researchers have also reported that younger women have positive feelings about menarche. 32,33 On the other hand, negative beliefs about menstruation were reported in different studies. [34][35][36] In principle, it seems difficult to understand the rarity of seeking medical care for a disease with physical load, psychological and social load comparable to that of some severe psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%